Lower chlorinated PCBs accumulate in demolition workers while working on a contaminated worksite - Stephanie C. Hammel; Vivi Schlünssen; David Hope; Mike Dereviankin; Courtney D. Sandau; Karin Sørig Hougaard; Harald W. Meyer; Pete Kines; Keld Alstrup Jensen; Marie Frederiksen (Environment International)
Several buildings in a Danish social housing estate exceeded indoor air guidance values for polychlorinated biphenyls (PCBs), leading to their demolition. Here, we conducted a biomonitoring study among the workers on-site (n = 24) to evaluate their exposure to all 209 PCBs across the two-year demolition. We compared their PCB serum concentrations and accumulation to those of demolition workers at other worksites (n = 21) and office workers (n = 17). Demolition workers were provided with personal protective equipment according to risk assessments for PCB-related work. Serum PCBs were measured from baseline and up to two annual follow-up visits using gas chromatography high-resolution mass spectrometry. Forty-six peaks representing 58 PCBs were detected in > 60 % of serum samples; eight congeners were found in every sample. PCB-153 was the most abundant congener (median = 22.1 ng/g lipid). After adjusting for age and smoking status, demolition workers after one year on the contaminated site experienced more than a four-fold increase in all lower chlorinated PCBs compared to office workers at baseline, with increases most prominent for tri- and tetra-CBs (10β = 6.2 and 9.2, p < 0.01). Nine PCBs were significantly elevated from baseline to year 1 in only contaminated-site demolition workers, with the largest increase observed for PCB-66/80. For higher chlorinated PCBs, levels remained consistent or decreased slightly over the three samples from these workers. Those who worked in active demolition for at least 4 years at baseline experienced a 40 % increase (95 % CI: 10 %, 90 %) in the WHO-12 PCB sum. Age significantly predicted increases in PCBs, which tracked closely with logKow values. Our study showed that despite safety measures, demolition workers who worked on a PCB-contaminated site experienced increased and accumulating internal exposure to lower chlorinated PCBs compared to general demolition and office workers. Consequently, workers’ safety should be carefully considered to reduce exposures among this high risk group.